2019
DOI: 10.1177/0731948719858683
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Effects of the Targeted Reading Intervention for Students With Low Phonological Awareness and/or Vocabulary

Abstract: Students most at risk for reading-related disabilities frequently struggle with word recognition and oral language, including, in the earliest grades, specific skills related to phonological awareness and vocabulary. Classroom teachers’ delivery of high-quality differentiated supplemental instruction may promote reading acquisition for these students. The current study examined whether the Targeted Reading Intervention, a webcam-coaching literacy professional development program for kindergarten and first grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…For instance, if the data from these assessments indicate that a small number of students have not yet acquired a specific set of reading skills, supplemental intensive instruction (tiers 2 or 3) that targets those skills can be implemented to that group of students (Adlof et al, 2017). Researchers have shown that supplemental targeted instruction (tiers 2 and 3) leads to positive reading performance outcomes for students (e.g., Benner et al, 2022; Bratsch‐Hines et al, 2020). Thus, the use of brief dyslexia rating scales such as those described here can be an efficient initial tool that prompts educators to conduct further assessments if necessary and design appropriate instruction for all students in the classroom.…”
Section: Implications For Classroom Instructionmentioning
confidence: 99%
“…For instance, if the data from these assessments indicate that a small number of students have not yet acquired a specific set of reading skills, supplemental intensive instruction (tiers 2 or 3) that targets those skills can be implemented to that group of students (Adlof et al, 2017). Researchers have shown that supplemental targeted instruction (tiers 2 and 3) leads to positive reading performance outcomes for students (e.g., Benner et al, 2022; Bratsch‐Hines et al, 2020). Thus, the use of brief dyslexia rating scales such as those described here can be an efficient initial tool that prompts educators to conduct further assessments if necessary and design appropriate instruction for all students in the classroom.…”
Section: Implications For Classroom Instructionmentioning
confidence: 99%
“…(2020), consideran que la relevancia de la conciencia fonológica, radica en que facilita la representación y manipulación de la estructura subléxica de las palabras habladas, proporcionando a los niños un nivel de comprensión efectivo sobre el principio alfabético de que las letras representan sonidos, según Bratsch-Hines et al (2019), los niños con conciencia fonológica pueden relacionar los sonidos con las letras de forma sistemática, favoreciendo en ellos, procesos como la decodificación y el análisis de palabras, aspectos clave para la adquisición de saberes; así pues, ellos pueden separar y combinar sonidos, inclusive les ayuda a sondear palabras desconocidas; de manera que, se asocia a la comprensión lectora.…”
Section: Selección De Estudiosunclassified
“…Para Yuan et al ( 2022), la clave está en empezar por lo más sencillo e ir avanzando paso a paso, teniendo en cuenta un andamiaje de acuerdo con la edad del niño, para luego, centrarse en unidades sonoras más amplias, como sílabas y rimas, antes de abordar fonemas individuales; de igual modo, se pueden realizar actividades multisensoriales y atractivas. En tal sentido, Bratsch-Hines et al (2019) recomiendan desde las actividades que se pueden coordinar en el aula, la utilización de estrategias de juegos y rimas infantiles, ya que, la aliteración en las rimas infantiles ayudan a los niños a reconocer y manipular los sonidos de las palabras; otra actividad, tiene que ver con tocar las sílabas de las palabras y contarlas, puesto que, permite a los infantes identificar dichas unidades sonoras más grandes; asimismo, la combinación de sonidos (g-a-t) y la segmentación de palabras en sonidos (gato = g-a-t) son ejercicios más avanzados pero 2020) aseguran que la información visual del habla obtenida de la lectura del habla contribuye al desarrollo de representaciones fonológicas en el cerebro, así pues, dichas representaciones favorecen en los niños el desarrollo de habilidades de conciencia fonológica, teniendo en cuenta, la flexibilidad y apoyo, a fin de superar las dificultades que enfrentan los niños con dislexia en el procesamiento fonológico, según refieren (Máñez-Carvajal y Cervera-Mérida, 2022). Por otro lado, es importante considerar que las habilidades de conciencia fonológica parecen estar favorecida en niños con un nivel socioeconómico medio, encontrándose que la conciencia fonológica, suelen estar influenciadas por aspectos como, las barreras culturales y de género, la falta de recursos y capacitación, expectativas poco realistas de los padres y falta de confianza en los niños; esto, aunado a lo señalado por Balbi et al (2020), en relación al vocabulario expresivo, ya que la conciencia fonológica y la correspondencia entre fonemas y grafemas se consideran predictores importantes en el desarrollo de la lectura en el nivel, no obstante, su investigación encontró que el poder predictivo de estos precursores disminuye con el paso del tiempo, por lo que se recomienda aprovechar la edad temprana del niño.…”
Section: Desarrollo De La Conciencia Fonológica En El Nivel Inicialunclassified
See 1 more Smart Citation
“…TRI’s one-on-one intervention delivery mechanism, such that teachers use intervention practices with individual selected students, helps teachers learn how to differentiate their reading instruction to benefit these students. Efficacy studies of TRI have demonstrated that students at risk for reading-related disabilities made significant reading gains across the school year after they participated in one-on-one TRI lessons with their classroom teacher (Vernon-Feagans et al, 2013, 2018; Bratsch-Hines et al, 2020). Prior TRI studies have primarily focused on if TRI produced gains for students.…”
mentioning
confidence: 99%